The Power of Educational leadership and School Culture: A Strategic Approach to Enhancing Teacher Performance through Job Satisfaction - Hamdani, Achmad; Soelistya, Djoko (Newinera Publisher, 2025)
The purpose of this research is to study things that influence teacher performance. Specifically, this research examines the influence of school culture and transformational educational leadership style on teacher performance, with job satisfaction as an intervention variable. The quantitative approach uses a saturated sampling method, where the entire population is sampled. The research method used in this research is quantitative research. The population in this study were all Teachers and Educational Staff of Yayasan Islam Malik Ibrahim (YIMI) Gresik and a saturated sample of 100 respondents. Data was collected through a questionnaire given to all Teachers and Educational Staff at Yayasan Islam Malik Ibrahim (YIMI) Gresik. The results of the research conducted show that Transformational Educational leadership Style has a significant influence on teacher performance, School culture has a significant influence on teacher performance, Transformational Educational leadership Style has a significant influence on job satisfaction, School culture has a significant influence on job satisfaction, Job satisfaction has a significant influence on teacher performance, and indirect influence Transformational educational leadership style has an influence on teacher performance through job satisfaction as full mediation, School culture has an influence on teacher performance through job satisfaction as full mediation. The results of this research indicate that transformational school culture and educational leadership style influence employee satisfaction and performance. Job satisfaction also contributes to improving teacher performance; in fact, good educational leadership and a positive school culture will increase job satisfaction, which in turn has an impact on overall teacher performance